Penerapan Profile Matching Dalam Sistem Pendukung Keputusan (SPK) Pemilihan Lokasi Strategis untuk Pembukaan Cabang Usaha - Darmansah, Darmansah; Harman, Rika; Amrizal, Amrizal (Journal of Information System Research (JOSH), 2025)
Batam is one of the cities with rapid economic growth supported by business, trade, and attractions. Many businesses are currently trying to expand their business by opening new branches. However, strategic locations for opening new branches are still a big challenge. Many entrepreneurs only rely on intuition or personal experience when making decisions, without considering strategic factors systematically, which risks business failure. Therefore, a system is needed to assist in decision making when choosing the best location. The purpose of this study is to apply the Profile Matching method in a Decision Support System (DSS) to assist business owners in choosing strategic locations in Batam. This method is used to compare ideal location criteria with field conditions based on 5 factors, such as population density, accessibility, level of competition, rental prices, and community purchasing power. The results of the study indicate that the Profile Matching method is able to identify the best location by comparing the weights between the ideal location profile and actual location data. The most strategic places for opening a business are Nagoya, Lubuk Baja and Batam Center with the highest total scores of 4.00, 3.50 and 2.00. With the Profile Matching-based SPK, business actors can reduce the risk of errors in choosing a location and increase the chances of their business success in Batam.